Municipal Sewage Treatment in 2050 - Stephenson, Tom (Cranfield University, 2009)
This Thinkpiece considers what the sewage treatment works of 2050 might look like. Factors that will influence the choice of flowsheet, such as sewerage infrastructure, carbon accounting and water use, are considered. Management of the sewage treatment flowsheet itself is predicted to be a major innovation, together with the use of novel unit operations.